Meniscus morphology: Does tear type matter? A narrative review with focus on relevance for osteoarthritis research - Jarraya, Mohamed; Roemer, Frank; Englund, Martin; Crema, Michel D.; Gale, Heather I.; Hayashi, Daichi; Katz, Jeffrey N.; Guermazi, Ali (Seminars in Arthritis and Rheumatism, 2017)
To give a narrative overview of meniscal tears with a radiologic emphasis on the morphologic type, technical considerations, and on the relevance of the type of meniscal tear in the context of osteoarthritis (OA) research.Total 20 years of the PubMed database were searched for epidemiological, radiological, arthroscopic and biomechanical reports, and review articles focusing on meniscal tears in middle-aged and older individuals, in the setting of OA. Case reports, publications on meniscal tears in young active individuals, and publications not in English were excluded.Meniscal intra-substance signal abnormalities are associated with an increased risk of a degenerative meniscal tear in the same segment. Posterior radial tears of the medial meniscus appear to be a highly relevant event in OA of the knee, with associated cartilage loss and meniscal extrusion. Radial tears are more commonly missed on MRI than other types, and should be carefully looked for on coronal and axial images. While medial meniscus posterior root tears are of "radial" morphology, there is growing interest in looking at them as a separate entity, mainly because they require a different therapeutic approach.There is a lack of data on the relevance of different morphologic types of meniscal tears to the natural history of knee OA, both cross-sectionally and-especially-longitudinally. Further epidemiologic studies should focus on specific meniscal tears based on their morphology to better understand their relevance in the genesis and progression of knee OA.
EVALuna2:14656